Verification of PCSWMM's LID processes and their scalability over time and space - Zhang, Zhonghao; Valeo, Caterina (Frontiers in Water, 2022)
This paper explores the scalability of PCSWMM’s Low Impact Development (LID) modelling tools within the urban stormwater computer model. The scalability is assessed for a variety of spatial and temporal scales and for event (50-year return storm) and continuous inputs (daily rainfall for an 11 month period), and with a focus on bioretention cells. The model is calibrated for a moderate to large scale, semi-urban watershed on Vancouver Island, British Columbia, Canada. Sensitivity analysis and specialized metrics are used to verify internal model processes at a variety of scales. With regard to spatial scaling, changes in flow path length and slope derived from Digital Elevation Models were the most impactful spatial information when modelling flood event and the model’s surface layer was the dominant contributor to peak flowrate and volume mitigation by the bioretention cell. However, when modelling the continuous rainfall inputs, storage layer related parameters dominated model outputs. Aside from the soil layer’s depth, soil layer parameters such as hydraulic conductivity, showed negligible influence on response to time series rainfall. Parameters that are kept static by the model such as vegetation cover, hydraulic conductivity and storage void ratio (but are naturally dynamic), were tested for their impact on response if allowed to change seasonally or with excessive loading. Runoff coefficients were greatly impacted by storage layer parameter dynamics with very little impact from vegetation. For event simulations, the berm height in the surface layer was the dominant player in reducing peak flow as well as total volume. An analysis to help illustrate sensitivity across spatial scales is proposed. The Spatial Dynamic Sensitivity Analysis shows that parameter sensitivity changes dynamically as LID implementation percentage changes. In particular, the clogging factor, which is a parameter associated with the storage layer, was highly influential for time series rainfall analysis. The LID model concepts in PCSWM seem appropriate for events because the surface layer dominates the response for very large storms. For smaller storms, continuous time series, and larger spatial scales, the model could be revised to better represent soil layer dynamics and vegetation cover, which were currently inconsequential to the model’s output.